Adoption of guidelines on and use of oral pre-exposure prophylaxis: a global summary and forecasting study. Issue 8 (August 2021) - Schaefer, Robin; Schmidt, Heather-Marie A; Ravasi, Giovanni; Mozalevskis, Antons; Rewari, Bharat B; Lule, Frank; Yeboue, Kouadio; Brink, Anne; Mangadan Konath, Nabeel; Sharma, Mukta; Seguy, Nicole; Hermez, Joumana; et al.
Summary: Background: In 2016, the UN General Assembly set a global target of 3 million oral pre-exposure prophylaxis (PrEP) users by 2020. With this target at an end, we aimed to assess global trends in the adoption of WHO PrEP recommendations into national guidelines and numbers of PrEP users, defined as people who received oral PrEP at least once in a given year, and to estimate future trajectories of PrEP use. Methods: In this global summary and forecasting study, data on adoption of WHO PrEP recommendations and numbers of PrEP users were obtained through the Global AIDS Monitoring system and WHO regional offices. Trends in these indicators for 2016–19 by region and for 2019 by country were described, including by gender and priority populations where data were available. PrEP user numbers were forecasted until 2023 by selecting countries with at least 3 years of PrEP user data as example countries in each region to represent possible future PrEP user trajectories. PrEP user growth rates observed in example countries were applied to countries in corresponding regions under different scenarios, including a COVID-19 disruption scenario with static global PrEP use in 2020. Findings: By the end of 2019, 120 (67%) of 180 countries with data had adopted the WHO PrEP recommendations into national guidelines (23 in 2019 and 30 in 2018). In 2019, there were about 626 000 PrEP users across 77 countries, including 260 000 (41·6%) in the region of the Americas and 213 000 (34·0%) in the African region; this is a 69% increase from about 370 000 PrEP users across 66 countries in 2018. Without COVID-19 disruptions, 0·9–1·1 million global PrEP users were projected by the end of 2020 and 2·4–5·3 million are projected by the end of 2023. If COVID-19 disruptions resulted in no PrEP user growth in 2020, the projected number of PrEP users in 2023 is 2·1–3·0 million. Interpretation: Widespread adoption of WHO PrEP recommendations coincided with a global increase in PrEP use. Although the 2020 global PrEP target will be missed, strong future growth in PrEP use is possible. New PrEP products could expand the PrEP user base, and, with greater expansion of oral PrEP, further adoption of WHO PrEP recommendations, and simplified delivery, PrEP could contribute to ending AIDS by 2030. Funding: Unitaid, Bill & Melinda Gates Foundation, and WHO.